Time-varying persistence in expected returns - Priestley, Richard (Journal of Banking & Finance, 2001)
This paper measures the extent to which persistence in expected returns moves asset prices. Over the period 1871–1997 persistence is found to vary greatly. For example, 1 unit of news about expected returns can have an impact between 2% and 30% on asset prices depending on the time period. Variations in persistence appear to be correlated with variations in the riskiness of the economy. That is, at times of high risk, news effects asset prices more than at times of low risk. These results have implications for the estimation of asset pricing models, tests of market efficiency and tests of present value models in general. Interestingly, we find that with the exception of the period surrounding the great depression and the second world war, volatility in stock prices is fairly constant and the time-variation in expected returns is driven by variations in the price of risk.